The Transmemoric Process: The Journey of Italian-Québécois Artists - Aloisio, Anita (Université Concordia, 2016)
The author focuses on the multilayered social identities internalized by seven second-generation Italian-Quebec artists and how it is manifested in their artwork. She examines how Quebec's political landscape, especially the impact of Quebec's linguistic, nationalist and cultural debates, and the subjects' parents' experience of immigration, impinged on the artistic process and production. The author demonstrates how these artists connect their Italian ethnicity to a creative practice to achieve a sense of balance between family traditions, personal identity, and belonging. The seven artists are: Vittorio Rossi (Playwright, Actor); Agata De Santis (Documentary Filmmaker, Producer, Blogger); Sandra Coppola (Filmmaker, Scriptwriter); Luisa Pepe (Singer, Songwriter); Franco Taddeo (Comedian); Michaela Di Cesare (Playwright, Actor); and Marco Calliari (Author, Composer, Musician).

La réception du hip-hop chez des rappeurs afro-québécois dans la ville de Québec : appropriation intersectionnelle de problématiques multidimensionnelles - Atséna Abogo, Marie Thérèse (Université Laval, 2016)